Review of historical earthquakes and survey of active faults in the San Leonardello Graben area, Mt. Etna (Sicily) - CARVENI, Pietro; BENFATTO, Santo; IMPOSA, Sebastiano; MANISCALCO, Rosanna; SALLEO PUNTILLO, Maria; STURIALE, Giovanni (Contributions to Geophysics and Geodesy, 2011)
Mount Etna is the largest active volcano in Europe, grown by accumulationof lavas and pyroclastics erupted by numerous vents during the last 180 kyr. It is locatedalong the Ionian coast of Sicily, on the margin of two main structural domains: theApennine-Maghrebian Chain to the north and the Hyblaean Foreland to the south. Whileeastern Sicily is characterized by a general uplift, the sector bounded by the North-East Rift and the Pernicana Fault northward, and by the Montagnola-Aci Castello FaultSystem toward SW is lowering; three more fault systems are active in the eastern sectorof Etna: i) the Giardini-Mascali Fault System (NE–SW and NNE–SSW trends); ii) theRipa della Naca-Piedimonte Fault System (NE–SW trend); iii) the Timpe Fault System(NNW–SSE trend). In historical times, the Giardini-Mascali Fault System was activeonly in 1847, while the Ripa della Naca-Piedimonte Fault System was active before andduring the 1865, 1928 and 1971 eruptions.Several earthquakes have occurred along the Timpe Fault System from 1805 to present.The analysis of seismological data and volcanic activity shows that the Timpe FaultSystem is the most active of the eastern flank of Etna. The most important faults of thissystem are the Moscarello, San Leonardello and Macchia-Stazzo Faults forming the SanLeonardello Graben. Shallow earthquakes occur along these faults, frequently causingsurface fractures. In this paper we analyze historical records of earthquakes strongerthan VII degree EMS-98. Macroseismic data are available since 1805. The epicentersare located along the northernmost segment of the faults. Along these faults offsets aremainly vertical with the maximum value of 80 cm recorded along the Moscarello Faultafter the 1911 Fondo Macchia Earthquake.